Negative Consequences of Alcohol Use among People Living with HIV. (12th May 2021) - Fisk, Rebecca J.; Richards, Veronica L.; Leeman, Robert F.; Brumback, Babette; Cook, Christa; Cook, Robert L.
Abstract: Introduction: Among people living with HIV (PLWH), alcohol use can have negative impacts beyond HIV-related outcomes. The objectives of this study are to identify the most common alcohol-related consequences among PLWH in Florida and describe factors associated with experiencing more alcohol-related consequences. Methods: Data were collected from PLWH in the Florida Cohort study who drank at least monthly in the past year (n=397). Self-reported consequences were assessed by the 15-item Short Inventory of Problems Revised (SIP-2R). Nonparametric tests and a generalized estimating equation model with inverse probability of exposure weighting were used to evaluate associations between the total SIP-2R score and socio-demographics, mental health, and substance use while controlling for alcohol use. Results: Over half (56%) endorsed at least one consequence and 29% endorsed 5 or more consequences. The most common consequences were doing something they regretted and taking foolish risks (both endorsed by 37% of participants), both in the impulse control domain. After controlling for alcohol use and other covariates, homelessness and injection drug use remained significantly associated with greater SIP-2R scores. Conclusion: PLWH who are experiencing homelessness or injecting drugs could benefit from receiving additional screening for alcohol-related consequences if they report any alcohol use.